Pengaruh Tes Standar dalam Menggabungkan 4C (Kolaborasi, Komunikasi, Kreativitas, dan Berpikir Kritis) di Kelas IPA - Lizoon Nahar (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this article was to investigate how the unintended side effects of standardized testing cause teachers not to integrate 21st century skills i.e., communication, collaboration, creativity, and critical thinking, into science classes. In addition, this study also cross-examineed if certain features of standardized testing have any beneficial impact on the adoption of 21st century skills in science teaching. Methodology: This paper followed the method of narrative review. 85 papers were initially selected after the primary searches. Finally, 30 papers were used to answer two research questions in this article. Main Findings: After analyzing the selected papers, this narrative review revealed three unintended outcomes of standardized testing on the practice of 21st century skills, which are: teachers often prioritize testing over teaching, which results in the fact that there is not enough time for innovative instruction, and the time spent on the actual content of the curriculum is often shortened. On the other hand, the review also found that standardized tests can motivate teachers and enable them to offer their students new opportunities to incorporate 21st century skills into science education by following Assessment guidelines and expanding curricular opportunities. Novelty/Originality of this study: This study revealed how standardized test-based education practices in science teaching can be analyzed and customized to create a space for cultivating 21st century skills for students.